Hypothetical Atopic Dermatitis-Myeloproliferative Neoplasm Syndrome - Kawakami, Toshiaki; Ando, Tomoaki; Kawakami, Yuko (Frontiers in Immunology, 2015)
Atopic dermatitis (AD) is a chronic inflammatory skin disease. Myeloproliferative neoplasms (MPNs) are hematopoietic malignancies caused by uncontrolled proliferation of hematopoietic stem/progenitor cells. Recent studies have described several mutant mice exhibiting both AD-like skin inflammation and MPN. Common pathways for skin inflammation encompass overexpression of thymic stromal lymphopoietin and reduced signaling of epidermal growth factor receptor in the epidermis, while overproduction of granulocyte-colony stimulating factor by keratinocytes and constitutive activation of Stat5 in hematopoietic stem cells are important for the development of MPN. The murine studies suggest the existence of a similar human disease tentatively termed the AD-MPN syndrome.